Assessment of seed quality in seed spices - P Balakrishna, P J Devaraju, C K Pramila, K P R Prasanna; Siddaraju, Siddaraju (Journal of Spices and Aromatic Crops, 2013)
The present study was carried out to assess seed quality of some important seed spices supplied in the local markets of Bengaluru. The results revealed that highest physical purity was recorded in fenugreek seed lots with an overall mean of 98.76% followed by fennel (97.99%) and coriander (97.68%). The moisture content of all the seed spices ranged from 6.89% to 7.15%. The highest seed germination (89.42%) was recorded in fenugreek followed by fennel (76.82%) and lowest (64.33%) in coriander. The seedling vigour index was highest in fenugreek (range 1116-1819; mean 1532) and lowest in cumin (range 621-832; mean 737). A 12.0% increase in germination and improvement in the vigour index (997-1226) were also noticed in treated seed samples compared to control (900).